Ba/Ca of stylasterid coral skeletons records dissolved seawater barium concentrations - Kershaw, James; Stewart, Joseph A.; Strawson, Ivo; de Carvalho Ferreira, Maria Luiza; Robinson, Laura F.; Hendry, Katharine R.; Samperiz, Ana; Burke, Andrea; Rae, James W.B.; Day, Russell D.; Etnoyer, Peter J.; Williams, Branwen; et al. (Chemical Geology, 2023)
Funding: Funding for this work was provided by a NERC GW4+ Doctoral Training Partnership studentship (NE/S007504/1) awarded to J.K., an Antarctic Bursary awarded to J.A.S, and NERC grants awarded to L.F.R. (NE/S001743/1; NE/R005117/1; NE/N003861/1). Cruise DY081 was funded by European Research Council starting grant ICY-LAB (Grant Agreement 678371). The concentration of dissolved barium in seawater ([Ba]SW) is influenced by both primary productivity and ocean circulation patterns. Reconstructing past subsurface [Ba]SW can therefore provide important information on processes which regulate global climate. Previous Ba/Ca measurements of scleractinian and bamboo deep-sea coral skeletons exhibit linear relationships with [Ba]SW, acting as archives for past Ba cycling. However, skeletal Ba/Ca ratios of the Stylasteridae – a group of widely distributed, azooxanthellate, hydrozoan coral – have not been previously studied. Here, we present Ba/Ca ratios of modern stylasterid (aragonitic, calcitic and mixed mineralogy) and azooxanthellate scleractinian skeletons, paired with published proximal hydrographic data. We find that [Ba]SW and sample mineralogy are the primary controls on stylasterid Ba/Ca, while seawater temperature exerts a weak secondary control. [Ba]SW also exerts a strong control on azooxanthellate scleractinian Ba/Ca. However, Ba-incorporation into scleractinian skeletons varies between locations and across depth gradients, and we find a more sensitive relationship between scleractinian Ba/Ca and [Ba]SW than previously reported. Paired Sr/Ca measurements suggest that this variability in scleractinian Ba/Ca may result from the influence of varying degrees of Rayleigh fractionation during calcification. We find that these processes exert a smaller influence on Ba-incorporation into stylasterid coral skeletons, a result consistent with other aspects of their skeletal geochemistry. Stylasterid Ba/Ca ratios are therefore a powerful, novel archive of past changes in [Ba]SW, particularly when measured in ...